A Grid-connected Hybrid Renewable Energy System Using High-frequency Multi-winding Transformer and Phase Shift Modulation Technique - Ramesh Kumar; Ravi Chandra; Anand Kumar (IAES Indonesian Section, 2021)
This paper presents a topology of multi-port phase-shift converter for integration of a PV system, a wind-turbine generator and a battery to supply a grid-connected domestic load. The main advantage of the topology is using a multi-winding high-frequency transformer to couple the input and outputs of the system. This simplifies the power flow control and provides isolation between the converter ports. Detailed operation of the proposed topology and the control system analysis are discussed. A numerical simulation of the proposed system is carried out to confirm the system operation and control technique.